Advancing PROMs for health system use in Canada and beyond - Michael Terner; Krista Louie; Candy Chow; Greg Webster (SpringerOpen, 2021)
Abstract PROMs are essential to delivering patient-centred health care, and when applied routinely they can enhance communication between patients and providers, inform decisions for value-based health system improvements and improve overall patient care experiences and outcomes. The use of patient-reported outcome measures (PROMs) across Canada varies across provinces and territories, partly because of differences in health care delivery models across these jurisdictions. A national program that coordinates uses of PROMs is needed to ensure that this information is comparable across jurisdictions. This commentary provides a summary look at the development of national PROMs data standards and reporting for hip and knee replacement surgery, including the selection of survey tools, building consensus, developing and promoting standards, and reporting on the results nationally and internationally as well as outlining recent learnings from regional implementation of data standards. In 2017, the Canadian Institute for Health Information published national PROMs data collection standards for hip and knee arthroplasty that included guidelines for survey time points, the minimum data set and PROMs instruments. This broad-scale PROMs collection initiative had stakeholder engagement and support from multiple levels within the health system, including administrators, clinic managers, patients, and health system decision-makers. Learnings from regional implementation of the standards demonstrated the importance of assessing existing infrastructure and information technology requirements, mapping clinical workflows, planning for human and information technology resources, navigating local legislation and hospital policies and ensuring data linkage capabilities. This initiative showed the need for a common regional approach for PROMs collection to be efficient and effective. The learnings from implementation of the national Canadian PROMs program for hip and knee arthroplasty can be used as an example for other jurisdictions and clinical areas such as renal care and mental health. Common data standards allow for secondary use of this data that is valuable for reporting and informing policy and guidelines as well as meeting care delivery goals to further the shift in health care systems becoming more patient-centred to improve the quality-of-life of patients.